Influência do herbicida Glifosato (N-Fosfonometil)Glicina) na formação de biomassa da alga Pseudokirchneriella subcapitata (Chlorophyceae) - Arantes, Poliana Beatriz [UNESP] (2010)
Herbicides are chemical agents most consumed for agricultural production and of these, glyphosate (N-(phosphonomethyl) glycine) represents more than half of world consumption of non-selective herbicides, use of systemic action and post-emergent. The present study aims to analyze the interference of different concentrations of glyphosate in the development of micro algae, unicellular species Pseudokirchneriella subcapitata, with supplementary analysis of the interference of green algae concentrations in the artificial lake Instituto de Biociências Universidade Estadual Paulista in Rio Claro, SP. To identify the effect of glyphosate on the development of microalgae concentrations: 0.118; 0.236; 0.472; 0.944; 1.888 and 3.776 mg of product (all in rejoinders), maintaining control without glyphosate, were inoculated into flasks containing 150mL of medium culture and 5mL of suspension inoculum levels. Each test was continued for 96 hours in a shaker rotating at 150 rpm at 25 / - 2 ° C and constant light of 3200 lux. At baseline and 48; 72 and 96 hours samples were taken for testing for absorbance. The final dry weight was measured and the tests with P. subcapitata cell number was quantified at the beginning and end of the tests using the Neubauer chamber under optical microscope. For algae of the artificial lake of the diversity of microalgae cells was identified through photographic documentation. The analysis of variance comparing treatments for dry biomass showed no significant differences in the tests with P. subicapitata as for the algae to the lake.The analysis of variance MANOVA showed significant differences between the treatments over time but there was no significant difference between the interactions of treatment for tests with P. subicapitata There were significant differences in the tests with microalgae of the artificial lake. With respect to cell quantification, it was found... (Complete abstract click electronic acces below)